2002
DOI: 10.1557/jmr.2002.0229
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Solution Deposition of Lanthanum Zirconate Buffer Layers on Biaxially Textured Ni–1.7% Fe–3% W Alloy Substrates for Coated-conductor Fabrication

Abstract: Sol-gel processing of La 2 Zr 2 O 7 (LZO) buffer layers on biaxially textured Ni-1.7% Fe-3% W alloy substrates using a continuous reel-to-reel dip-coating unit has been studied. The epitaxial LZO films obtained have a strong cube texture and uniform microstructure. The effects of increasing the annealing speed on the texture, microstructure, and carbon content retained in the film were studied. On top of the LZO films, epitaxial layers of yttria-stabilized zirconia and Ceria (CeO 2 ) were deposited using rf sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…The sample was then additionally annealed in the protective atmosphere at 1025°C for 1 h (condition A2). This temperature is within the range of that frequently used for buffer layer crystallization [13,[15][16][17][18]. It is pertinent to mention that no evidence of secondary recrystallization was found in the given sample even when additional annealing was conducted at 1100°C for 1 h. Vickers microhardness was measured in the annealed samples using a load of 200 g with a 15 s dwell time.…”
Section: Methodsmentioning
confidence: 86%
“…The sample was then additionally annealed in the protective atmosphere at 1025°C for 1 h (condition A2). This temperature is within the range of that frequently used for buffer layer crystallization [13,[15][16][17][18]. It is pertinent to mention that no evidence of secondary recrystallization was found in the given sample even when additional annealing was conducted at 1100°C for 1 h. Vickers microhardness was measured in the annealed samples using a load of 200 g with a 15 s dwell time.…”
Section: Methodsmentioning
confidence: 86%
“…In this paper we explore the possibility of combining a single buffer layer prepared by a waterbased CSD technique with a YBCO layer produced by MOCVD. Other authors have reported the possibility of using single LZO layers (MOD) in combination with pulsed laser deposited YBCO [11] or MOCVD YBCO [12,13]. The crystallographic and superconducting properties of this coated conductor are studied together with an extensive analysis of the interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In the RABiTS approach, a four-layer architecture of -W is used to fabricate long lengths of buffered tapes by epitaxial deposition on the thermomechanically textured alloy [5]. Typically, these layers are grown via a combination of vacuum processes, such as rf magnetron sputtering, and nonvacuum chemical solution deposition (CSD) processes, such as sol-gel deposition or metal-organic deposition (MOD) [6]. A simpler 3-layer RABiTS architecture of -W, in which the seed layer is deposited using MOD, has also been reported [7].…”
Section: Introductionmentioning
confidence: 99%